Data-Driven Continuous Assessment of Frailty in Older People - Martini, Chiara; Barla, Annalisa; Odone, Francesca; Verri, Alessandro; Cella, Alberto; Rollandi, Gian Andrea; Pilotto, Alberto (Frontiers in Digital Humanities, 2018)
The process of aging affects an individual’s potential in several dimensions, encompassing the physical, cognitive, psychological, economic, and social domains. The assessment of frailty in elderly patients is key to estimate their overall well-being and to predict mortality risk. In the clinical practice, frailty is usually estimated through medical tests and questionnaires performed sporadically. Continuous automatic assessment may help physicians in evaluating frailty by complementing their assessments with quantitative and non sporadic measurements. In this paper, we present the state-of-the-art in frailty evaluation, we summarize recent research achievements that could lead to an improved assessment, and we illustrate a case study we are conducting in our institution. Finally, based on our experience and results, we comment on the open challenges of automatic assessment of frailty.